Audit Plan as an Instrument to Improve the Effectiveness of Tax Audits - KUSUMA, I Gede Komang Chahya Bayu Anta; ARIBOWO, Irwan; SUPRIYADI , Supriyadi; KUMAR, Jai; KAMILAH, Niswatun Nurul (Journal of Governance, Taxation and Auditing, 2025)
Tax audits are an integral part of implementing the self-assessment system. The tax audit phase begins with preparatory activities, such as developing an audit plan. The audit plan encompasses several activities that must be carried out as a guideline for conducting tax audits. This study aims to determine the role of audit plans in improving the effectiveness of tax audits, particularly during the planning stage. This research used a descriptive qualitative approach, involving in-depth interviews with tax auditors and data analysis using the NVivo application. The results indicate that problem identification has been developed for each audit assignment based on available data and information. A risk-based audit plan strategy is implemented to direct the audit focus and ensure the application of methods, techniques, and procedures to obtain competent and sufficient evidence. The use of technology, such as the Derik application, facilitates audit plan development and more structured risk identification. Currently, detailed and focused audit plans help improve audit effectiveness by providing a deterrent effect and successfully obtaining competent and sufficient audit evidence that can be accounted for in the event of a tax dispute. However, the audit team's utilization of audit plans is still suboptimal, impacting audit effectiveness. This study recommends strengthening the implementation of risk-based audit plans and optimizing technology in tax audits.